2015
DOI: 10.1586/14737167.2015.1047349
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) in combination with gemcitabine in metastatic pancreatic cancer in Spain: results of the PANCOSTABRAX study

Abstract: The PANCOSTABRAX study evaluated the cost-effectiveness of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) in combination with gemcitabine (GEM) versus GEM alone in the treatment of patients with metastatic pancreatic cancer in Spain. Efficacy data were obtained from the MPACT study and were modeled to a lifetime horizon using a Markov model. The analysis was performed from the payer's perspective. Use of resources and key assumptions of the analysis were validated by a panel of oncologists. The additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…They reported that GEM-NAB is more cost-effective than GEM alone. Carrato et al 24 and Gharaibeh et al 25 reported similar results. In contrast, from the perspective of US healthcare payers, Gharaibeh et al 25 reported that GEM-NAB is less cost-effective than GEM.…”
Section: Discussionmentioning
confidence: 57%
“…They reported that GEM-NAB is more cost-effective than GEM alone. Carrato et al 24 and Gharaibeh et al 25 reported similar results. In contrast, from the perspective of US healthcare payers, Gharaibeh et al 25 reported that GEM-NAB is less cost-effective than GEM.…”
Section: Discussionmentioning
confidence: 57%
“…Lazzaro et al 7 performed a cost-effectiveness analysis of GnP compared with G in unresectable pancreatic cancer from the perspective of Italian payers. They reported that GnP is more costeffective than G. Carrato et al 8 and Gharaibeh et al 9 reported similar results. In contrast, from the perspective of US healthcare payers, Gharaibeh et al 10 reported that GnP is less cost-effective than G.…”
Section: Introductionmentioning
confidence: 74%
“…We estimated the disutility from a previous study. 8 In addition, disutility was applied only to "survival of progression-free state. "…”
Section: Utilitymentioning
confidence: 99%
“…ABI-007 is a new polyoxyethylated castor oil-free formulation of paclitaxel developed to overcome the limitations attributed to the solvent Kolliphor EL (previously called Cremophor EL) and improve the therapeutic index and safety profile of solvent-based paclitaxel (sb-P) [ 9 ]. Peripheral neuropathy (PN) is the major toxicity related to taxanes [ 6 , 10 , 11 , 12 ]. Although it is not completely clear how taxanes cause PN, in vitro studies have demonstrated that taxanes interrupt axonal transport mediated by microtubules, leading to neuropathy [ 13 ].…”
Section: Introductionmentioning
confidence: 99%